2004
DOI: 10.1080/1071576042000206487
|View full text |Cite
|
Sign up to set email alerts
|

Photo-irradiated Titanium Dioxide Catalyzes Site Specific DNA Damage via Generation of Hydrogen Peroxide

Abstract: Titanium dioxide (TiO2) is a potential photosensitizer for photodynamic therapy. In this study, the mechanism of DNA damage catalyzed by photo-irradiated TiO2 was examined using [32P]-5'-end-labeled DNA fragments obtained from human genes. Photo-irradiated TiO2 (anatase and rutile) caused DNA cleavage frequently at the guanine residue in the presence of Cu(II) after E. coli formamidopyrimidine-DNA glycosylase treatment, and the thymine residue was also cleaved after piperidine treatment. Catalase, SOD and bath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(148 citation statements)
references
References 40 publications
4
143
0
1
Order By: Relevance
“…In practice, surfaces coated with the photocatalyst titanium dioxide (TiO 2 ), which can be activated by UV light to release DNA damaging oxygen radicals 24 including hydrogen peroxide, 25 have also been shown to limit bacterial biofilm development. Similarly, glass surfaces treated with photocatalytically active TiO 2 also resist bacterial adhesion in the presence of UV light.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, surfaces coated with the photocatalyst titanium dioxide (TiO 2 ), which can be activated by UV light to release DNA damaging oxygen radicals 24 including hydrogen peroxide, 25 have also been shown to limit bacterial biofilm development. Similarly, glass surfaces treated with photocatalytically active TiO 2 also resist bacterial adhesion in the presence of UV light.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies regarding the PC inactivation mechanism mainly focused on the specification of the roles of extracellular ROSs. Studies investigating the bactericidal effect of intracellular ROSs are very limited, although intracellular ROSs are believed to be responsible for the oxidative damage of enzymes 14 and DNA, 15 and potentially play very important roles in cell damage during PC inactivation of microorganisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 In the work of Lu et al, quantum dots of ∼5 nm in diameter were observed to be able to penetrate E. coli cells exposed to TiO 2 with 20 min illumination, suggesting the destruction of the cell envelope (i.e., cell wall and cell membrane) and the leakage of intracellular macromolecules. 18 The leaked proteins and nucleic acids from bacterial cells are believed to be oxidatively damaged or segmented and further attacked by extracellular-and intracellular-produced ROSs, 14,15 leading to degradation and complete mineralization. However, identifying the details of cell leakage or specific damage to biomolecules, such as proteins and nucleic acids, was rarely attempted in PC inactivation systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Also, free TiO2 particles can attack intracellular components directly if it is enhanced with UV irradiation. This may lead to physical and chemical damages of DNA and RNA, causing the conversion of the pyrimidine and purine bases to carbon dioxide, ammonia and nitrate ions [23,24]. Although there are at least three hypotheses of the antimicrobial effect of TiO2 photocatalytic reaction, that mechanism is still to be proved.…”
Section: Results and Discussion Anti-bacterial Activitymentioning
confidence: 99%